Student project monitoring system (SPMS) using text recognition / Muhammad Firdaus Mustapha ...[et al.] - Mustapha, Muhammad Firdaus; Ahmad, Marina; Ab Hamid, Siti Haslini; Mohamad, Roslim; Mohd Zin, Nor Asma; Nik Wan, Nik Zam (2019)
Recently, most of the courses at the university require students to complete a specific project within a given timeline. Some courses contain several projects that have to be completed in several phases. Therefore, managing and monitoring students project can be nontrivial. One of the solutions to simplify project monitoring is by developing a system that can monitor progress of student project. Thus, we design and develop a student project monitoring system known as SPMS. The uniqueness of the proposed system is it integrates text recognition algorithm into student project monitoring system. At the same time, the proposed system has advantage to simplify student project monitoring process rather than manual process especially during report submission for each project phases. It also can be accessed online through any web browser. As a result, the proposed work is capable to monitor progress of student project effectively for students and lecturers. The proposed work can be implemented in relevant industry such as in monitoring the worker’s task